2020
DOI: 10.1039/d0sm01257b
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory structural forces between charged interfaces in solutions of oppositely charged polyelectrolytes

Abstract: Forces between negatively charged micron-sized silica particles were measured in aqueous solutions of cationic polyelectrolytes with the atomic force microscope (AFM). In these oppositely charged systems, damped oscillatory force profiles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…For instance, the forces induced by PEs between two charged surfaces show oscillating behaviors . Many experiments have shown that the oscillating interactions are related to the occurrence of charge reversal and inversion on the charged surfaces. In general, due to the challenge of singling out the effects of individual variables, it is difficult to explore the origins of the rich and complicated behaviors in nanoconfined PE systems by only using experimental techniques . However, as complementary approaches, theories and simulations allow for facile control of the factors that influence the force behaviors between two charged surfaces induced by PE solutions. , Using Monte Carlo simulations, Pegado et al and Guldbrand et al found that the ion–ion correlations make the counterions adsorb more at the charged walls and thus reduce the electric double layer overlapping, which results in a shorter range of the interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the forces induced by PEs between two charged surfaces show oscillating behaviors . Many experiments have shown that the oscillating interactions are related to the occurrence of charge reversal and inversion on the charged surfaces. In general, due to the challenge of singling out the effects of individual variables, it is difficult to explore the origins of the rich and complicated behaviors in nanoconfined PE systems by only using experimental techniques . However, as complementary approaches, theories and simulations allow for facile control of the factors that influence the force behaviors between two charged surfaces induced by PE solutions. , Using Monte Carlo simulations, Pegado et al and Guldbrand et al found that the ion–ion correlations make the counterions adsorb more at the charged walls and thus reduce the electric double layer overlapping, which results in a shorter range of the interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillatory structural forces in dispersions of charged colloidal particles were extensively studied for ionic micelles (Nikolov and Wasan, 1989;Bergeron and Radke, 1992;Richetti and Kékicheff, 1992;McNamee et al, 2004;Tulpar et al, 2006;Tabor et al, 2011a;Tabor et al, 2011b;James and Walz, 2014;Ochoa et al, 2021), polyelectrolytes (Milling and Vincent, 1997;Klitzing et al, 1999;Qu et al, 2006;Biggs, 2010;Üzüm et al, 2011;Browne et al, 2015;Moazzami-Gudarzi et al, 2017;Kubiak et al, 2020), and solid nanoparticles (Piech and Walz, 2002;Piech and Walz, 2004;Drelich et al, 2006;Zeng et al, 2011;Schön and von Klitzing, 2018;; experimental evidence for oscillatory structural forces in dispersion of uncharged particles is available for aqueous solutions of nonionic surfactants (Basheva et al, 2007;Christov et al, 2010) and latex particles (Basheva et al, 1997;Crocker et al, 1999).…”
Section: Introductionmentioning
confidence: 99%